Impact of Chronic Kidney Disease Stages on Hematological Parameters: Insights from a Tertiary Care Hospital - Asaduzzaman, Md; Alam, MM Jahangir; Mahmud, Md Jakaria; Karim, Md Rezaul; Roy, Soumitra; Roy, Ranjon Kumer; Islam, Mohammad Nazrul; Islam, Khandaker Mohammad Rezwanul; Das, Sushanta; Chowdhury, Mohammad Alamgir (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Chronic Kidney Disease (CKD) is a global health concern characterized by progressive kidney dysfunction, often leading to various hematological abnormalities. This study was designed to assess the impact of CKD stages on hematological parameters in patients attending a tertiary care hospital. Methods: This cross-sectional study was conducted at Sylhet MAG Osmani Medical College Hospital from April 2019 to March 2020. A total of 60 predialytic CKD patients (Stages 3 to 5) were included. Patients on hemodialysis, with hematological disorders, recent hemorrhagic events, blood transfusions, or evidence of recent infection were excluded. Sociodemographic data, hematological parameters and clinical information were collected and analyzed. Statistical analyses, including descriptive statistics, Spearman correlation, ANOVA and regression analyses were performed to evaluate the relationships between CKD stages and hematological parameters. Results: A total of 60 CKD patients were enrolled in the study, with a mean age of 53.7 years. Significant negative correlations were observed between CKD stages and hemoglobin levels (r = -0.515, p < 0.001), RBC count (r = -0.481, p < 0.001) and total WBC count (r = -0.092, p = 0.481). Regression analysis revealed that for each increase in CKD stage, hemoglobin levels decreased by an average of 1.717 g/dL (p < 0.001), while RBC counts decreased by 0.577 million cells/μL (p = 0.006) and WBC counts decreased by 1.702 thousand cells/μL (p = 0.011). Platelet count showed no significant changes (p = 0.834). Conclusion: The findings of this study highlight the significant impact of CKD stages on hematological parameters, particularly hemoglobin and RBC counts. J Bangladesh Coll Phys Surg 2025; 43: 145-153